Detection and Identification of Mammalian Reoviruses in Surface Water by Combined Cell Culture and Reverse Transcription-PCR - Spinner, Michael L. (American Society for Microbiology, 2001)
Reoviruses are a common class of enteric viruses capable of infecting a broad range of mammalian species, typically with low pathogenicity. Previous studies have shown that reoviruses are common in raw water sources and are often found along with other animal viruses. This suggests that in addition to the commonly monitored enteroviruses, reoviruses might serve as an informative target for monitoring fecal contamination of drinking water sources. Mammalian reoviruses were detected and identified by a combined cell culture–reverse transcription-PCR (RT-PCR) assay with novel primers targeting the L3 gene that encodes the λ3 major core protein. Five of 26 (19.2%) cytopathic effect-positive cell culture lysates inoculated with surface water were positive for reoviruses by RT-PCR. DNA sequence analysis of RT-PCR products revealed significant sequence diversity among isolates, which is consistent with the sequence diversity among previously characterized mammalian reoviruses. Sequence analysis revealed persistence of a reovirus genotype at a single sampling site, while a sample from another site contained two different reovirus genotypes.